Comparing the Electrical Activity of some of the Striking Arm Muscles and the Accuracy of Serving Performance between Volleyball and Tennis - Alwan, Bahera; Gassim, Talb; Akrim, Sarab (Journal of Physical Education, 2013)
This study interested in comparing the activity of the triceps muscle and the flexor muscle of the wrist (Carpi radialis muscle) of the striking arm while performing the skill of straight serving in tennis and overhand serving in volleyball. The participation of the muscle in the motion was recorded after studying its signals using the (EMG) of the muscles; the Bluetooth. The most important aims of the study is to identify the differences of the electrical activity in the two muscles in term of serving accuracy, peak, space and time between lawn tennis players and Iraqi clubs volleyball players. The researchers suggested there were statistically significant differences in the electrical activity of the two muscles in term of serving accuracy, peak, space and time between lawn tennis players and Iraqi clubs volleyball players. The study was conducted on a sample of (18) players (including 9 players classified in the first ranks from the Iraqi national team of lawn tennis and 9 players from Iraqi clubs of volleyball). The main conclusions of the study, however, confirmed that there is no significant differences in the peak and space of the triceps muscle electricity in term of accurate serving for lawn tennis players and overhand serving for volleyball players. In the other hand, time variable of muscle electricity itself has explored some significant differences in accurate serving for tennis players while there is no significant difference in the peak, space and time of flex. wrist muscle electricity in term of accurate serving for lawn tennis players and of overhand serving for volleyball players. The most important recommendations emphasized on raising the level of performance of the striking arm muscles in serving skills for tennis and volleyball in order to reach the highest peak and less space which leads to better performance with economy of effort.